The ebb and flow of protons: A novel approach for the assessment of estuarine and coastal acidification. (5th May 2020) - Pettay, D. Tye; Gonski, Stephen F.; Cai, Wei-Jun; Sommerfield, Christopher K.; Ullman, William J.
Abstract: The acidification of estuarine and coastal waters is a consequence of both natural (e.g., aerobic respiration) and anthropogenic (e.g., combustion of fossil fuels, eutrophication) processes and can negatively impact the surrounding ecosystems. Until recently it was difficult to accurately measure pH, and thus total proton concentrations ( [ H T + ] ), when salinities vary significantly and rapidly as a consequence of tidal mixing. Proton production and transport are ultimately responsible for acidification in nearshore environments, and the uncertainty surrounding proton concentrations measured at high frequency has hindered our understanding of the net impact of global and local processes on estuarine and coastal acidification. Here, we quantify the rate of proton exchange between an estuary and bay to assess the extent of acidification by using the novel combination of high frequency pHT (total hydrogen ion concentration scale) data from an autonomous SeapHOx™ sensor and continuous tidal discharge measurements made between the eutrophic Murderkill Estuary and Delaware Bay. Proton fluxes reverse with each tide. However, the net non-tidal proton fluxes are directed upstream and display seasonal changes in magnitude. Our results indicate that Delaware Bay contributes to the acidification of the Murderkill Estuary, yet the degree of acidification is reduced in the summer. Using proton concentrations measured at high temporal resolution to calculate proton fluxes provides a new and relatively simple approach for quantifying the acidification of dynamic nearshore environments. Highlights: Proton production and transport are responsible for estuarine acidification. Proton fluxes (mmol/h) were quantified between an estuary and bay. Fluxes calculated using high frequency [H+] and tidal discharge measurements. Non-tidal proton fluxes are directed upstream with seasonal changes in magnitude. Delaware Bay contributes to the acidification of the Murderkill Estuary.